Effects of a Mathematics Fluency Program on Mathematics Performance of Students With Challenging Behaviors. Issue 2 (2nd April 2016) - Whitney, Todd; Hirn, Regina G.; Lingo, Amy S.
Abstract : In the present study, we examined the effects of a fluency-building mathematics program called Great Leaps Math on fluency of basic addition mathematics facts zero to nine and word problem solving using a multiple probe design across participants. Three elementary students with challenging behaviors and mathematics difficulty participated in the study. Results showed that all three students increased their oral fluency of basic mathematics facts and word problem solving skills, with one student increasing written fluency and written generalization fluency (e.g., problems displayed vertically and horizontally).